Luminescence and cytotoxic study of red emissive europium(III) complex as a cell dye - Canisares, Felipe S.M. [UNESP]; Mutti, Alessandra M.G. [UNESP]; Cavalcante, Dalita G.S.M. [UNESP]; Job, Aldo E. [UNESP]; Pires, Ana M. [UNESP]; Lima, Sergio A.M. [UNESP] (Elsevier, 2022)
A novel non-toxic red luminescent Eu(III)-complex, (Na[Eu(Fmpc)4(H2O)4]∙3H2O), based on a carboxylic acid ligand was synthesized and characterized by several techniques, such as elemental analysis, MALDI TOF spectrometry, thermogravimetric analyses, UV–vis, FT-IR, and photoluminescence spectroscopies; also its structure was optimized theoretically by the AM1 sparkle model. The Gd(III)-complex, (Na[Gd(Fmpc)4(H2O)3]∙4H2O), was also synthesized and characterized, to evaluate the Fmpc ligand triplet excited state, revealing that the energy of the ligand is suitable to sensitize the similar Eu(III)-complex, indicating a high sensitization rate of the Fmpc ligand to Eu3+ ion with 98% efficiency. The Na[Eu(Fmpc)4(H2O)4]∙3H2O luminescent properties were investigated, and its excited state lifetime was also determined as 0.76 ms in acetonitrile solution. The complex relative quantum yield was estimated to be 27.9%, evidencing that the Fmpc ligand is efficient in transferring the absorbed energy to the europium(III) ion emitting level. Furthermore, the cytotoxicity of Na[Eu(Fmpc)4(H2O)4]∙3H2O was tested in CHO-k1 cells by the MTT assay, and no cytotoxicity was observed at 24 h of exposure within the concentrations tested (25–200 µg/mL). Its use for cell imaging was also evaluated by fluorescence and confocal microscopies. Our findings indicated that Na[Eu(Fmpc)4(H2O)4]∙3H2O complex exhibited great luminescent properties, it is non-toxic, and it has potential for bioimaging application as a luminescent dye.
Keywords: Cell imaging; Confocal microscopy; Lanthanides; Non-toxic; Rare earth; Red emitter